Statistical study of maximum temperature at Poona with special reference to forecasting of weekly maximum temperature - RAGHAVENDRA, V. K. (MAUSAM, 1956)
Seventy two years' maximum temperature data of Poona have been studied in this paper. The co-efficients of variability of mean monthly maximum temperatures have maxima in June and October, The frequency distribution of daily maximum temperature during April and May have been studied and found to be skew. The curved dz/dx=kzm (l-z)n has been fitted to the frequency distribution. The inter monthly correlations between the mean maximum temperatures have been found, The winter months are highly correlated, The interweekly correlation during that winter months have been calculated, The regression formulae for forecasting of weekly maximum temperature for the week Nos,46, 47,48,49, 50,51,52,1,2 and 3 of the Grower's year based on the weekly maximum temperatures of the preceding four weeks have been worked out, arid comparative diagrams are given. Also the frequency of spells months with mean maximum temperature above and below the corresponding normal were worked out and the persistency of months of either type has been studied.